Perayaan Maulid PErspektif Sosiologi Agama - Saidun Derani (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
The celebration of MAulid is very related to Islamic aspects (dimentions). So it can mot be taken away from itssocial institution to maintain social solidarity. This celebration is a fact an dsocial behavior in certain communitythat becomes its social charecteristic and not contrasted with islamic teaching. This event an be analyzed thoough sociologicaltheory/approach, Symbolic interaction, and phenomenology.